DECREASING PREVALENCE OF THE ACUTE/SUBACUTE CLINICAL FORM OF PARACOCCIDIOIDOMYCOSIS IN MATO GROSSO DO SUL STATE, BRAZIL - Fabris, Larissa Rodrigues; Andrade, Ursulla Vilella; Santos, Aline Ferreira Dos; Marques, Ana Paula da Costa; Oliveira, Sandra Maria do Valle Leone de; Mendes, Rinaldo Poncio; Paniago, Anamaria Mello Miranda (Revista do Instituto de Medicina Tropical de São Paulo, 2014)
With the objective to evaluate the behavior of paracoccidioidomycosis in the last three decades, clinical and epidemiological data of 595 patients admitted to clinical services of the Federal University of Mato Grosso do Sul from 1980 to 2009 were investigated. Gender, age distribution, clinical form, comorbidity with tuberculosis or AIDS, and mortality were compared by decades of clinical admission. It was shown that during the three decades there was a decrease in women percentage, and the same manner occurred a reduction in participants in the age group of 20 to 39 years. Moreover, the acute/subacute forms have been diminished in the period. These fluctuations are closely related and can be simultaneously analyzed. Increased AIDS co-infection prevalence from the first to the second decade was also revealed, coinciding with the appearance of the retroviral epidemic and stabilizing during the third decade. No change in the tuberculosis co-infection rate was observed (overall = 6.9%). It reinforces the importance of this co-morbidity. The overall mortality rate remained steady at 6.7%, not varying significantly from one decade to another. The persistent mortality rate calls attention to the importance of this neglected disease.